2017
DOI: 10.1103/physreva.96.062504
|View full text |Cite
|
Sign up to set email alerts
|

Casimir and Casimir-Polder forces with dissipation from first principles

Abstract: We consider Casimir-Polder and Casimir forces with finite dissipation by coupling heat baths to the dipoles introducing, this way, dissipation from 'first principles'. We derive a representation of the free energy as an integral over real frequencies, which can be viewed as an generalization of the 'remarkable formula' introduced by Ford et. al. 1985. For instance, we obtain a nonperturbative representation for the atom-atom and atom-wall interactions. We investigate several limiting cases. From the limit T → … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…It is interesting to mention that in [30] it was seen that formulas like (22)- (24) give the complete free energy, i.e., including that of the polarizable fluid and the heat bath. It was also shown that this is the complete free energy of the system if the dissipation is switched off.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to mention that in [30] it was seen that formulas like (22)- (24) give the complete free energy, i.e., including that of the polarizable fluid and the heat bath. It was also shown that this is the complete free energy of the system if the dissipation is switched off.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to study properties of quantum entanglement, long range effect of field correlations, Unruh effect etc. The spacetime curvature can alter the Casimir-Polder interaction [23][24][25] between the atoms [26] in two body OQS. The CPI in the de Sitter spacetime [27] has been investigated in detail in refs [15,[28][29][30].…”
Section: Assumption IVmentioning
confidence: 99%
“…For an overview of the implications for Casimir-Polder interactions, see Reiche & al. (2020); Bordag (2017).…”
Section: A Derivation Of Hydrodynamic Parametersmentioning
confidence: 99%